Desenvolvimento de sensores colorimétricos baseados em compostos amido/cera de abelha e antocianinas por casting contínuo para embalagens inteligentes - Luchesi, Bruno Ribeiro (Universidade Federal de São Carlos, 2023)
Intelligent packaging are systems capable of communicating the conditions of the packed food and different approaches can be used to produce such packaging, for instance, the production of quality indicators based on components that change their color when stimulated by the environment. Among these, anthocyanins stand out as non-toxic natural compounds whose color is pH dependent. Colorimetric films containing anthocyanins can be obtained using starch as a polymeric matrix, an abundant, eco-friendly, and low-cost natural polymer. However, starch films have low resistance to moisture, which is worsened upon anthocyanins incorporation. In this thesis, it was proposed the obtaining of colorimetric sensory films based on starch and anthocyanin extracts incorporated with beeswax (30%, m/m) as a hydrophobizing agent. The films were obtained by continuous solution casting to scale up their production, thus filling the scientific gap in suitable processing techniques for colorimetric sensors based on anthocyanins. The scientific perspective of this thesis was expanded by exploring hibiscus, banana bracts, and jaboticaba peels as sources of anthocyanins and their influence on the physical properties and performance of the starch sensors. The incorporation of extracts and beeswax modified the mechanical properties of the films, whose tensile strength and elastic modulus being 60% and 70% lower, respectively, and elongation at break 400% greater than those of films containing only the extracts. Furthermore, the presence of beeswax reduced the water vapor permeability by 40% and increased surface hydrophobicity in 70% of the sensory films, but without significantly influencing their optical properties. All starch/beeswax/anthocyanin films were sensitive to NH3, a volatile compound released during the rotting of some foods, at a concentration equal to 100 µg m-2, guaranteeing their potential application in intelligent packaging.
Development of colorimetric sensors based on starch/beeswax compounds and anthocyanins by continuous casting for intelligent packaging
Keywords: Embalagens biodegradáveis; Indicadores de qualidade; Hidrofobização; Compostos poliméricos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA